The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/0102-33062014abb3064
|View full text |Cite
|
Sign up to set email alerts
|

Pre-dispersal seed predation and abortion in species of Callisthene and Qualea (Vochysiaceae) in a Neotropical savanna

Abstract: The ability of plants to generate fertile offspring is influenced by morpho-physiological and ecological factors. Hence, reproductive success is directly linked to factors affecting quantity and quality of their progeny. In the Cerrado (savanna) of Brazil, the Vochysiaceae is a widely distributed and ecologically important family. Factors affecting pre-dispersal seed predation and abortion were studied for populations of Callisthene fasciculata, C. major, Qualea multiflora and Q. parviflora. To characterize di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
(77 reference statements)
2
12
0
Order By: Relevance
“…There was also substantial within-species variation among years (e.g. 8.2 % and 15.9 % of seed predation in two years for Copaifera langsdorffii) (Souza & Fagundes 2017) and sites (0 % and 51.3 % seed predation in two different sites for Callisthene major) (Custódio et al 2014) (Tab. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There was also substantial within-species variation among years (e.g. 8.2 % and 15.9 % of seed predation in two years for Copaifera langsdorffii) (Souza & Fagundes 2017) and sites (0 % and 51.3 % seed predation in two different sites for Callisthene major) (Custódio et al 2014) (Tab. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The literature review indicated great among-species variation in the amount of seed predation, from 0 % in Callisthene fasciculate (Custódio et al 2014) up to 100 % in Eriotheca grassilipes (Francisco et al 2008) (Tab. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Callisthene fasciculata reaches between 4 and 15 m in height, and has a thick, dark, and highly rough bark (Pott & Pott, 1994). The flowering period takes place between September and October, together with the dispersion of seeds generated in the previous year (Custódio et al, 2014). It is a deciduous species with absent leaf fall during the periods of high water and receding water up to the beginning of dry season, followed by partial and total deciduousness that begins in the dry season and lasts until the beginning of the rising water period (Corsini & Guarim-Neto, 2000).…”
Section: Study Areamentioning
confidence: 99%